2013
DOI: 10.4103/0972-5229.117058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition in a tertiary care hospital in India

Abstract: Introduction:Malnutrition adversely affects clinical outcome of hospitalized patients. This observational prospective study was done to assess the prevalence of malnutrition and its grade among patients admitted in a mixed intensive care unit (ICU) of a tertiary care hospital in order to help devise a comprehensive nutrition program for the malnourished.Materials and Methods:A total of 500 sequential patients admitted to the ICU were screened on admission over a year period for malnutrition using the Subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
(10 reference statements)
2
20
0
1
Order By: Relevance
“…This may be due to low sample size in this age group and need more representative study to confirm it. Dominguez [2] also found that older patients (above 60 years) were more malnourished and it was supported by Chakravarty, et al [22] and Kruizenga, et al [7] also. But Naderi, et al [14] found younger patients (18-29 year) to be more malnourished.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This may be due to low sample size in this age group and need more representative study to confirm it. Dominguez [2] also found that older patients (above 60 years) were more malnourished and it was supported by Chakravarty, et al [22] and Kruizenga, et al [7] also. But Naderi, et al [14] found younger patients (18-29 year) to be more malnourished.…”
Section: Discussionsupporting
confidence: 58%
“…Many studies have used combination of BMI and intention weight loss as screening tools to identify diseases related malnutrition [16,22], some used BMI alone [23,24] and others both criteria were used [2,25,26]. This study revealed that the prevalence of DRM was 25.9% and 21.0% at tertiary care settings respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Poor nutritional status includes under-nutrition and malnutrition states. It has been reported that the prevalence of malnutrition in acutely hospitalized adults is approximately 50% in these countries (3,16). Malnutrition is an important problem that increases mortality and morbidity.…”
Section: Pathophysiology Of Malnutritionmentioning
confidence: 99%
“…Intensive care unit patients are considered to be malnourished when their food (protein, carbohydrates, and lipids) supply is not enough to meet their metabolic requirements (3). The causes of malnutrition in patients in ICU are multifactorial.…”
Section: Pathophysiology Of Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation